المبادئ العـامة ضمانات لتحقيـق المحاكـمة الدولية العـادلة The General Principles Guarantees To Achieve A Fair International Trial - دحية, عبد اللطيف (Université de M'sila, 2018)
تهدف هذه الدراسة إلى محاولة توضيح أهم المبادئ لضمان تحقيق محاكمة دولية عادلة، وقد قمنا بتقسيمها لجزئين، في الجزء الأول تحدّثنا عن مبدأين مهمين وهما مبدأ شرعية الجرائم و العقوبات وكذا مبدأ المساواة أمام القضاء أو ما يسمى بمبدأ عدم التمييز، في الجزء الثاني من هذه الدراسة تحدثنا عن مبدأي استقلالية القضاء وافتراض البراءة باعتبارهما كذلك مبدأين أساسيين لضمان محاكمة دولية عادلة، و في الأخير ختمنا دراستنا هذه بخاتمة تضمنت بعض النتائج و التوصيات. Abstract: This study aims to clarify the most important principles for ensuring a fair international trial, and we divided it into two parts. In the first part, we discussed two important principles: the principle of the legality of crimes and penalties and the principle of equality before the judiciary or the principle of non-discrimination. In the second part of this study we spoke of the principles of judicial independence and the presumption of innocence as fundamental principles for ensuring a fair international trial. Finally, we concluded our study with a conclusion that included conclusions and recommendations.
Keywords: مبادئ، ضمان، محاكمة دولية عادلة. General principles, guarantees, a fair, international, trial.